Commemorating the 30th anniversary of the ratification of the Antarctic Treaty, and encouraging U.S. support of an international agreement to close the Antarctic to commercial mineral development for 99 years : report together with dissenting views (to acompany H. Con. Res. 109) (including cost estimate of the Congressional Budget Office) - United States. Congress. House. Committee on Interior and Insular Affairs. ([Washington, D.C.? : U.S. G.P.O., 1991)
"April 30, 1991"--Pt. 1. Caption title. Mode of access: Internet. 17